Mathematics learning independence: The relationship of youtube as a media for mathematics learning - Isnaini, Jihan Fitri; Azhar, Ervin (Universitas Islam Negeri Raden Intan Lampung, 2021)
This research aims to determine whether there is a relationship between YouTube social media and student learning independence. This research was conducted through a quantitative approach using ex-post facto research methods. The sampling technique used was cluster random sampling. The validity of the instrument was tested using expert judgment and empirical test using Product Moment/Pearson. The instrument was tested using the Cronbach Alpha formula. The data obtained were analyzed using descriptive statistics, prerequisite test analysis, and correlation analysis. Based on theoretical studies and calculations of the two variables, it shows that there is a positive relationship between YouTube social media on student learning independence and the magnitude of the YouTube social media relationship on student learning independence.